Bioactive glass plus laser phototherapy as promise candidates for dentine hypersensitivity treatment. Issue 1 (1st October 2015) - Lopez, Talita Christine Camilo; Diniz, Ivana Márcia Alves; Ferreira, Leila Soares; Marchi, Juliana; Borges, Roger; de Cara, Sueli Patricia Harumi Miyagi; D'Almeida‐Couto, Roberta; Marques, Márcia Martins
Abstract: Treatments for dentine hypersensitivity (DH) may produce positive effects, though do not have lasting results. We investigated the reparative potential of stem cells derived from deciduous teeth (SHEDs) in response to components delivered from substances used in the treatment of the DH, associated or not to laser phototherapy (LPT), to stimulate dentine formation. SHEDs were submitted to substances delivered from a laboratorial P‐rich bioactive glass [57SiO2 −26CaO‐17P2 O5 (wt %)] or a commercially available desensitizer (Gluma® Desensitizer), associated (or not) to LPT (InGAlP diode laser, 660 nm, 0.028 cm 2, 20 mW, 5 J/cm 2, 7 s, contact mode). Biomaterial characterization was performed by X‐ray diffraction, scanning electron microscopy and the particle size was evaluated by dynamic light scattering. SHEDs proliferation and differentiation were analyzed by MTT and Alizarin Red staining, respectively. The conditioned media used in these tests were evaluated regarding their pH and the ionic concentration changes due to ions leached from the bioactive glass (BG). BG majority presented a non‐crystalline solid structure and mixed particle sizes characterized by the agglomeration of nanoparticles. Cultures treated with BG alone or in association to LPT showed improved cell growth in relation to Gluma ® ( p  < 0.05). Gluma ® was cytotoxic in all tested conditions, regardless irradiated or not. BG associated to LPT induced intense mineral matrix formation. In conclusion, BG releases ionic dissolution products able to promote SHEDs differentiation. BG associated to LPT improves SHEDs proliferation and differentiation in vitro, and may be a promise therapeutic approach for the DH treatment. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 107–116, 2017.